Integrated Community-Based Education and Screening for Cardiometabolic Risk Prevention among Women’s Community Group - Melinda Yuslian; Fariza Yulia Kartika Sari; Noor Azizah; Rizka Himawan (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The growing prevalence of noncommunicable diseases (NCDs), particularly hypertension and diabetes mellitus, is closely associated with modifiable cardiometabolic risk factors, including obesity, unhealthy dietary behaviors, and physical inactivity. Early detection and improved health literacy are essential to reducing the burden of these conditions. This community service program evaluated the effectiveness of an integrated health education and screening intervention in improving health knowledge and identifying cardiometabolic risk factors among community participants. A one-group pretest–posttest design was implemented with 40 participants. The intervention combined educational sessions on hypertension, diabetes, obesity, healthy nutrition, and physical activity with health screening, including blood pressure, random blood glucose, body weight, height, and body mass index assessments. Program effectiveness was assessed by comparing pre- and post-intervention knowledge scores. Participants’ mean knowledge score increased significantly from 68.95 ± 14.73 to 77.50 ± 14.68 (p < 0.001), indicating improved health literacy following the intervention. Health screening further identified a considerable proportion of participants with overweight or obesity, hypertension, and elevated blood glucose levels, highlighting the need for early preventive measures. These findings demonstrate that integrating community-based health education with routine cardiometabolic screening is an effective strategy for enhancing health literacy while facilitating the early detection of NCD risk factors. The intervention provides a practical and scalable model for strengthening community-based NCD prevention and promoting long-term public health outcomes.